BANTUAN PELAYANAN ADMINISTRASI DALAM KEGIATAN IMUNISASI DI DESA GANTAR, KABUPATEN INDRAMAYU - Abdur Rahim; Ulla Sabrina; Gina Sapitri; Muhammad Haekal; Arif Budiman; Nasywa Aqilah Haya; Khansa Silmi Nabilah; Farhan Roiddin (Jurnal Abdimas Bina Bangsa, 2023)
Community Service can be used as a place for students to develop. Knowledge can not only be obtained in the classroom, outside students can also meet new people, exchange knowledge, and learn something that students have not and cannot get on campus. Experience outside the campus is able to make students grow, both in terms of soft skills, hard skills, to networking. The purpose of community service activities is in the form of administrative service assistance in immunization activities in order to prevent an increase in maternal and infant mortality during pregnancy, childbirth or afterward. As for the implementation of administrative service assistance in immunization activities for toddlers using the survey method, namely collecting data on toddlers and pregnant women by giving routine immunizations to infants and periodic health checks for pregnant women to determine the health of infants and pregnant women. The result of this activity is that the provision of immunization to toddlers which has been carried out is an activity for toddlers, especially toddlers in Gantar Village, Indramayu Regency which can help the development of toddlers well. This program is expected to provide knowledge for parents so that they are more aware of the importance of immunization for toddlers to form a generation that is physically and mentally healthy, and is beneficial for the Puskesmas and Villages in terms of administering immunization results for local residents, so that the village government can control the health development of residents, especially toddler